Kemampuan berpikir kreatif matematis siswa SMA pada materi statistika - Irmayanti Irmayanti; Harry Dwi Putra (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to analyze students' mathematical creative thinking skills. Indicators of mathematical creative thinking ability are fluency, flexibility, authenticity and detail in statistical material. The subjects of the study were 30 class XII students in one of the West Bandung Regency High Schools. The research method uses descriptive qualitative to describe students' creative thinking process through classroom learning. The research instrument consists of a description test of 4 questions and a questionnaire of 10 questions. Processing test and questionnaire data using Microsoft Excel 2019. Based on the results of the study, it was obtained that students' mathematical creative thinking skills were in the medium category. In the smoothness indicator, a percentage of 85% was obtained, while the flexibility indicator obtained a percentage of 80%, then for the Authenticity indicator 78% and the 4th indicator Keterinci got a percentage of 68%.